Estudio del patrimonio intangible del centro histórico de Latacunga - Torres Lozano, Erick Santiago (2024)
The intangible cultural heritage has been recognized as a crucial element for demonstrating people's cultural identity. This heritage not only preserves cultural diversity, but also promotes creativity and enrichment at living culture. The fundamental aim this project is to study the Intangible Cultural Heritage from Latacunga historic center. To reach this purpose, it was set 3 specific aims; The first has to do with analyzing the historical, social, cultural and political aspect, this research has a historical approach, descriptive type. For the second aim, which is treated by making the Intangible Cultural Heritage inventory, it was used an ethnographic methodology was used and the instructions for the sheets and Intangible Cultural Heritage inventory as a guide. Moreover, the snowball technique use allows identifying the knowledge carriers, same that leads to mapping and executing the respective interviews. For the third aim, which was to design a cultural guide to Intangible Heritage, it was used the descriptive methodology, what implies an information exhaustive analysis, which went to capture in the guide. This methodology allows a intangible heritage elements detailed and accurate description, what is going to present, thus guaranteeing an adequate and complete understanding this important aspect from culture. The research results revealed the notable intangible cultural wealth present in the Latacunga historic center. It was identified areas and sub-areas, what reflect this richness, including legends and oral expressions in scope A1, traditional games in scope A2, festivities in scope A3, gastronomy in scope A4, and traditional craft techniques, such as saddlery, locksmithing, and watchmaking in scope A5. The inventory process from the Intangible Cultural Heritage 26 records culminated in the development a cultural guide, which will function as a tool to disseminate the cultural manifestations present in the historic center. Its purpose is to raise awareness among residents about the importance by preserving the customs, traditions and religious festivities from Latacunga historic center.